Geometric Design in Islamic Architecture: Examination of Tessellation Configurations in Mosques - Takva, Çağatay; Takva, Yenal (Journal of History Culture and Art Research, 2023)
Tessellation is a mathematical concept used in geometric design. As in many fields, this method is also encountered in architecture. In this study, it is aimed to investigate the tessellation configurations in marble and wooden-columned mosques within the scope of geometric design in architecture, to show the effectiveness of geometry in the architectural production in these buildings, and to draw attention to the relationship between tessellation and geometry in Islamic buildings. The research question of the study is how tessellation configurations are applied in marble and wooden-columned mosques in Islamic architecture and how this relationship is established. Depending on this research question, Beyşehir Eşrefoğlu Mosque, Sivrihisar Ulu Mosque, and Konya Alâeddin Mosque in Turkey were examined within the scope of this study. The common point of these Islamic buildings is the use of tessellation patterns in the minbar and mihrab sections. Content analysis was performed by looking at the architectural features of the marble and wooden-columned mosques and geometric analysis of the tessellation configurations in the minbars and mihrabs was conducted with the data obtained. As a result, it has been seen that various variations in tessellation configurations are used in marble and wooden-columned mosques, which are products of Islamic architecture. The academic study in which the tessellation method is emphasized in mosques is limited. Therefore, this study will fill the gap in the literature.